Multi-complex attributes analysis for optimum GPS baseband receiver tracking channels selection - Rahmatullah, Bahbibi (N/A, 2017)
Multi-complex attributes analysis for optimum GPS baseband receiver tracking channels selection by Rahmatullah, Bahbibi